The regulatory role of INSIG1 in testicular Sertoli cells in boars - Shaoxuan Zhang; Hang Zhou; Simin Liu; Jing Li; Dali Wang; Boxing Sun; Hao Sun; Shuang Liang (Theriogenology, 2026)

Low-visibility scene enhancement for promoting vessel traffic safety in intelligent maritime surveillance - Boxing Zhang; Jingxian Liu; Junxiong Liang; Ryan Wen Liu (Ocean Engineering, 2026)

Bottom-up self-assembly of Ti3C2T /SA aerogel for highly efficient dyes wastewater purification - Boxing An; Feihong Chu; Yaze Zhang; Xu Liu; Yushan Li; Beiyun Liu; Haiyan Liu (Journal of Environmental Chemical Engineering, 2025)

Effect of temperature on the radon release characteristics of red clay - Chao Gu; Qiang Sun; Lei Zhang; Liwei Zhang; Duoxing Yang; Boxing Yang; Zhenlong Ge (Journal of Environmental Radioactivity, 2024)

Lysine-specific demethylase 1 (LSD1) participate in porcine early embryonic development by regulating cell autophagy and apoptosis through the mTOR signaling pathway - Jiajia Qi; Shaoxuan Zhang; Hexuan Qu; Yanqiu Wang; Yanwei Dong; Huakai Wei; Yu Wang; Boxing Sun; Hao Jiang; Jiabao Zhang; Shuang Liang (Theriogenology, 2024)

Strategies for Dissecting the Genetic Driving of Conserved Noncoding-Elements for Evolutionary Development of the Corpus Callosum - Yaxin Ye; Boxing Jin; Hao W. Zhang; Nengyin Sheng (Neuroscience Bulletin, 2024)

Effects of PM2.5 and its constituents on hemoglobin during the third trimester in pregnant women - Guilan Xie; Jie Yue; Wenfang Yang; Liren Yang; Mengmeng Xu; Landi Sun; Boxing Zhang; Leqian Guo; Mei Chun Chung (Environmental Science and Pollution Research, 2022)
Anemia has been a public health issue evoking global concern, and the low hemoglobin (Hb) concentration links to adverse pregnancy outcomes. However, the associations of PM 2.5 and its constituents with Hb and anemia in pregnant women remain unclear. In this retrospective birth cohort study, 7932 pregnant women who delivered in the First Affiliated Hospital of Xi’an Jiaotong University from 2015 to 2018 were included. The Hb during the third trimester in pregnant women was assessed before delivery. PM 2.5 and its constituents (BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust) during pregnancy were retrieved from the V4.CH.03 product constructed by the Atmospheric Composition Analysis Group. Generalized linear regression model was applied to investigate the effects of PM 2.5 and its constituents on Hb and anemia during the third trimester in pregnant women. The means and standard deviations of PM 2.5 , BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust were 69.56 (15.24), 10.02 (2.72), 8.11 (1.77), 14.96 (5.42), 15.36 (4.11), 10.08 (1.20), and 10.98 (1.85) μg/m 3 , respectively. Per IQR increase (μg/m 3 ) of PM 2.5 , BC, NO 3 − , and OM linked to − 0.75 (− 1.50, − 0.01), − 0.85 (− 1.65, − 0.04), − 0.79 (− 1.56, − 0.03), and − 0.73 (− 1.44, − 0.03) g/L decrease of Hb during the third trimester in multiparous pregnant women, but not for NH 4 + , SO 4 2− , Dust, and primiparous pregnant women. PM 2.5 and its constituents had no significant association with anemia, except for Dust (OR: 0.90, 95% CI: 0.82, 0.99, per IQR increase) in primiparous pregnant women. Besides, SO4 2− was of lag effects on Hb and anemia in multiparous pregnant women. Moreover, non-linear associations were found among PM 2.5 and its constituents, Hb, and anemia. Therefore, exposure to PM 2.5 and some constituents of PM 2.5 was associated with reduced Hb level during the third trimester in multiparous pregnant women. Related departments and pregnant women should take targeted actions to eliminate the detrimental effects of PM 2.5 and its constituents on pregnancy outcomes.

Bioinformatic analyses of a potential Salmonella-virus-FelixO1 biocontrol phage BPS15S6 and the characterisation and anti-Enterobacteriaceae-pathogen activity of its endolysin LyS15S6 - Han Han; Xuemin Li; Tingting Zhang; Xiaoqing Wang; Jiaojiao Zou; Chunxia Zhang; Huiling Tang; Yanyan Zou; Boxing Cheng; Ran Wang (Antonie van Leeuwenhoek, 2019)